2021
DOI: 10.24203/ajas.v9i1.6558
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of Organic Amendments on Heavy Metals Adsorption in Soils and their Chemical properties

Abstract: Incubation experiment was carried out to evaluate and compare effects of some selected amendments on adsorption of heavy metals in soils and their chemical properties. The experiment was CRD consisting of twelve treatment combinations with three replications. Soil samples were collected from the vicinity of Michael Okpara University of Agriculture and amended with organic amendments at the rate 20 ton/ha and heavy metals at the rate of 60 mg/kg, thoroughly mixed and wetted daily throughout the incubation perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2121
2121

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Low level of organic carbon may be due to rapid organic matter weathering in the tropics, bush burning in the area and intensive utilization of the soils for agricultural crop production with short fallowing period for soil recuperation and regeneration of botanical biodiversity. These soils will be low in CEC due to their low organic content as Nwachukwu et al (2021) defined soil organic matter as a complex and heterogeneous mixture of organic substances that provide much of the CEC and water holding capacity of soils. Different observation was also made on organic carbon by Akpan-Idiok et al (2016) who reported moderate values of organic carbon for similar soils in Cross River State.…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…Low level of organic carbon may be due to rapid organic matter weathering in the tropics, bush burning in the area and intensive utilization of the soils for agricultural crop production with short fallowing period for soil recuperation and regeneration of botanical biodiversity. These soils will be low in CEC due to their low organic content as Nwachukwu et al (2021) defined soil organic matter as a complex and heterogeneous mixture of organic substances that provide much of the CEC and water holding capacity of soils. Different observation was also made on organic carbon by Akpan-Idiok et al (2016) who reported moderate values of organic carbon for similar soils in Cross River State.…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…It has also been reported that using organic amendments, such as cow manure or sewage sludge in heavy metalspolluted soils, may increase the soil sorption properties and thereby decrease the heavy metal availability [19,20]. However, the long-term decomposition of these compounds can redistribute heavy metals in the soil, which can be a negative aspect [21,22]. Accordingly, using organic amendments, such as Multi-Walled Carbon Nanotubes (MWCNs), can increase the soil sorption properties without changing soil components.…”
Section: Introductionmentioning
confidence: 99%